(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The present experiment was conducted at the Agronomy Field, Patuakhali Science and Technology University, Patuakhali during the period from July to December 2012 to study the effect of modern varieties and number of seedlings hill1 on the yield of Transplant Aman rice where six modern varieties viz. BR 11, BR 23, BRRI dhan40, BRRI dhan44, BINA dhan7 and BRRI dhan52 and three levels of seedlings number hill1viz. 3, 5 and 7 seedlings hill1 were used under the tidal non-saline ecosystem. Results revealed that the interaction between varieties and seedling number hill1, the highest grain yield (6.15 t ha1) and straw yield (8.10 t ha1) were recorded from the variety BR 23 with 5 seedlings hill1. The highest number of effective tillers hill-1 (9.067) and 1000 grain weight (29.31 g) contributed to the highest yield in this treatment combination. Results suggested that the variety BR 23 is suitable with 5 seedlings hill-1 for higher yield under tidal non-saline ecosystem of Patuakhali. These significant variation results on yield and yield components may also be attributed to variation in genetic performance and the variation in their seedlings number hill1 under regional adaptability of tidal non saline ecosystem of Patuakhali region. DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22119 J. Environ. Sci. & Natural Resources, 6(2): 201-205 2013